PENGEMBANGAN BAHAN AJAR IPA BERBASIS E-BOOK MATERI SISTEM PERNAPASAN PADA MANUSIA PADA SISWA KELAS VIII DI SMP NEGERI 2 SIAU TIMUR SELATAN - Anggi Ifanda Selamat; Jovialine A Rungkat; Ester C. Wowor (LPPM Politeknik Saint Paul Sorong, 2023)
This research aims to develop a product in the form of ebook based science teaching materials on the human respiratory system at the SMP Negeri 2 Siau Timur Selatan and to determine the feasibility of ebook based science teaching materials on the human respiratory system at the SMP Negeri 2 Siau Timur Selatan. Type of Research And Development with the development model by Borg and Gall, namely (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) trial (test try small gorups). This research was conducted in the even semester of the 2022/2023 academic year. Data collection was carried out by interviews and questionnaires. This succeeded in (1) producing a media product in the form of ebook based science teaching materials on the human respiratory system at the SMP Negeri 2 Siau Timur Selatan, (2) The ebook was declared suitable for use with an average score of 97% for all aspects of the material, 95% for media experts, 92% for teacher responses as users, and 93% for student responses as users, so that the suitability of the ebook based science teaching materials developed is included in the category “very good”.